Szeneninterpretation unter Verwendung multimodaler Sensorik und Salienzmaßen - Müller, Markus (Schriftenreihe Automatische Sichtprüfung und Bildverarbeitung, 2022)
The work deals with aspects of image and video exploitation for monitoring, surveillance and security applications in non-cooperative application situations. The term "non-cooperative" refers to scenarios in which, for example, the recording parameters (backgrounds, lighting conditions, etc.) are not or hardly known. The goal is to detect man-made modifications (artifacts) in natural environments.